STRENGTHENING RELIGIOUS MODERATION TO SUPPORT HUMAN VALUES (RELIGIOUS PHILANTHROPY IN MODERATION VILLAGE) - Munawiroh; Saepudin, Juju; Badruzzaman; Suharsongko, Edi; Ta’rif; Basri, Husen Hasan; Arief, Hanief; Priyono (Veredas do Direito, 2026)
This describes human values in strengthening religious moderation carried out by a group of religious extension workers at the moderation village community in Tangerang Selatan. Human values supporting religious moderation are reflected in community generosity in helping someone or community members who need help to build love for fellow humans. That aspect of charity is manifested through the framework of religious Philanthropy. This research is a case study using data sources from interviews, observations, documentation, and literature studies. Data processing uses descriptive-analytical methods, namely research that seeks to describe, record, analyze and interpret the conditions in moderate village communities to knit human values through religious Philanthropy carried out by religious and community extension workers. Religious extension workers seek to integrate human values through the community's generosity in the village of moderation. To ensure that the public can still understand the mainstreaming of religious restraint, more concrete efforts and support from all parties are needed to realize the Ministry of Religious Affairs' policies to realize a peaceful and prosperous society.